Using endemic freshwater fishes as proxies of their ecosystems to identify high priority rivers for conservation under climate change. (May 2020) - Yousefi, Masoud; Jouladeh-Roudbar, Arash; Kafash, Anooshe
Graphical abstract: Highlights: We quantified the impacts of climate change on the distribution of 15 endemic freshwater fishes. We found that five species will lose their current suitable range under climate change while ten species will gain new suitable habitats. We identified 20 high priority rivers for conservation under climate change. Abstract: Freshwater ecosystems are among the most endangered ecosystems on Earth and are vulnerable to climate change. Studies have shown that climate change has already altered the phenology and distribution of freshwater species. However, there are still major gaps in our understanding of potential impacts of climate change on freshwater ecosystems and their organisms. Freshwater fishes were used as effective indicators for identifying the degree, direction and scale of changes in aquatic ecosystems and as indicators of freshwater ecosystem quality and health. However, they are rarely used to determine sensitive freshwater ecosystems to climate change using species distribution modeling. We modeled current and future distribution of 15 endemic freshwater fish in Iran to identify winners and losers of climate change and high priority rivers for conservation under climate change. In addition, we assessed changes in elevational distribution of the species under climate change. Our results showed that five species will lose some parts of their current suitable range under climate change while ten species will gain new suitable habitats. Considering their restricted range, endemic species are of special conservation concern, so results of this study can be used for conservation of endemic freshwater fishes. Species which were identified to be negatively affected by climate change should be prioritized for monitoring and conservation and can be the subject of future conservation programs. Using the five species for which reductions of range size were predicted, 20 rivers were identified as targets of future conservation actions to reduce negative impacts of climate change on freshwater fish.